CHEMICAL COMPOSITION AND ANTIOXIDANT ACTIVITY OF ANGELICA (Angelica archangelica L.) ROOT ESSENTIAL OIL AND EXTRACTS - Stanojević, Jelena; Simonović, Nataša; Djordjević, Silvija; Stanojević, Ljiljana; Zvezdanović, Jelena; Cvetković, Dragan (Archives of Pharmacy, 2023)
The present study aimed to compare the chemical composition and antioxidant activity of isolates (essential oil, tea infusion, ethanolic, and hexane extract) obtained from the dried angelica root (Angelicae radix; Angelica archangelica L.). The plant material was purchased from the Institute for Medicinal Plants Research "Dr. Josif Pancic". The essential oil was isolated by Clevenger hydrodistillation; the tea was prepared according to the instructions given on the package, while the ethanol and hexane extracts were obtained by Soxhlet extraction. The qualitative and semi-quantitative composition of the essential oil was determined by the GC/MS method, while the chemical composition of the obtained extracts was determined by the UHPLC-DAD-ESI-MS method. The contents of total phenols and total flavonoids in the extracts were determined by the Folin-Ciocalteu method and the AlCl3 method, respectively, while the antioxidant activity of the obtained isolates was determined by the DPPH test. Based on the GC/MS results, the most abundant compounds in the essential oil were fatty acids with palmitic (23.6%) and linoleic acid (26.5%) as representatives and coumarins, with ostol (12.6%) as the dominant compound. UHPLC chromatography of angelica root extracts in positive ionization mode enabled the identification of coumarins (ostol) and furanocoumarins (xanthoxin, bergapten, psoralen, and angelicin). The values of total phenols and total flavonoids decreased in the order: ethanol extract > tea infusion > hexane extract.